Sublimation growth of ALN bulk crystals and high-speed CVD growth of SiC epilayers, and their characterization - Lu, Peng (Kansas State University, 2006)
The effects of process conditions on the material’s properties were investigated for the sublimation growth of aluminum nitride and the epitaxial growth of silicon carbide. Since the mid 1990’s, these semiconductors have made new types of high power electronics and short wavelength optoelectronics that were never before feasible. The sublimation growth of AlN crystals on SiC seeds was carried out to produce high quality AlN bulk crystals. Si-face, 3.5 º off-axis 6H-SiC (0001) and 8 º off-axis 4H-SiC (0001) wafers were used as the substrates. An investigation of the initial growth demonstrated 1800 – 1850ºC was the optimum temperature for AlN growth. By optimizing the temperature gradient, large area AlN layer was deposited. Consecutive growths and continuous growth were performed to enlarge the crystal thickness. Single-crystalline AlN layers, each with a thickness of 2 mm and a diameter of 20 mm, were produced. X-ray diffraction confirmed the grown AlN had good crystal quality. Approximately 3 – 6 at% of Si and 5 – 8 at% of C were detected in the crystals by x-ray photoelectron spectroscopy, which came from the decomposition of SiC seeds and the degradation of the graphite components in the furnace. Molten KOH/NaOH etching revealed the dislocation density decreased from 108 cm-2 to 106 cm-2 as the AlN layer thickness increased from 30 μm to 2 mm. Epitaxial growth of SiC was carried out in a chemical vapor deposition system. High-quality 6H-SiC and 4H-SiC homoepitaxial films were produced at growth rates up to 80 μm/hr by using a novel single precursor, methyltrichlorosilane (MTS). Inclusions of 3C-SiC were circumvented by employing 8º mis-orientated substrates. Adjusting the H2/Ar flow ratio in the carrier gas effectively changed the C/Si ratio in the gas phase due to the reaction between H2 and the graphite heater; thereby, influencing surface roughness and dislocation density. Low H2/Ar ratios of 0.1 and 0.125 produced smooth surfaces without step-bunching. Higher H2/Ar ratios of 0.2 and 0.33 enhanced the conversion of basal plane dislocations into threading edge dislocations, and reduced the density of basal plane dislocations to approximately 600 cm-2.
Keywords: Aluminum nitride; Sublimation; Silicon carbide; Chemical vapor deposition; Engineering, Materials Science (0794)